Remnants of Serbo-Croatian Lexis in Present-day Croatian - Lečić, Dario (Slavia Centralis, 2020)
This article deals with the process of language purism and the presence of Serbisms in Croatian. We attempt to show whether the speakers of Croatian know and use specific lexical items that are generally considered to be more characteristic of Serbian usage. For this purpose we use two data sources: a corpus of Croatian and a questionnaire survey. The results show that the speakers of Croatian are aware of the differences between Croatian and Serbian to a large extent. Even though they mostly do not use them, most speakers do know the meaning of lexemes that were used in the Serbo-Croatian period. This leads to the conclusion that the process of “cleansing” Croatian is being successfully implemented (but is far from completion). However, we argue against the justifiability of this process.
Keywords: Croatian; Serbian; Serbisms; language purism; lexis